Image-guided biopsy in the esophagus through comprehensive optical frequency domain imaging and laser marking: a study in living swine. - Suter MJ; Jillella PA; Vakoc BJ; Halpern EF; Mino-Kenudson M; Lauwers GY; Bouma BE; Nishioka NS; Tearney GJ (Gastrointestinal Endoscopy, 2010)
BACKGROUND: Random biopsy esophageal surveillance can be subject to sampling errors, resulting in diagnostic uncertainty. Optical frequency domain imaging (OFDI) is a high-speed, 3-dimensional endoscopic microscopy technique. When deployed through a balloon-centering catheter, OFDI can automatically image the entire distal esophagus (6.0 cm length) in approximately 2 minutes. OBJECTIVE: To test a new platform for guided biopsy that allows the operator to select target regions of interest on an OFDI dataset, and then use a laser to mark the esophagus at corresponding locations. The specific goals include determining the optimal laser parameters, testing the accuracy of the laser marking process, evaluating the endoscopic visibility of the laser marks, and assessing the amount of mucosal damage produced by the laser. DESIGN: Experimental study conducted in 5 swine in vivo. SETTING: Massachusetts General Hospital. MAIN OUTCOME MEASUREMENTS: Success rate, including endoscopic visibility of laser marks and accuracy of the laser marking process for selected target sites, and extent of the thermal damage caused by the laser marks. RESULTS: All of the laser-induced marks were visible by endoscopy. Target locations were correctly marked with a success rate of 97.07% (95% confidence interval, 89.8%-99.7%). Thermal damage was limited to the superficial layers of the mucosa and was observed to partially heal within 2 days. LIMITATIONS: An animal study with artificially placed targets to simulate pathology. CONCLUSIONS: The study demonstrates that laser marking of esophageal sites identified in comprehensive OFDI datasets is feasible and can be performed with sufficient accuracy, precision, and visibility to guide biopsy in vivo.